Four cases of orthostatic myoclonus. (July 2016) - Aldaajani, Z.; Chang, F.C.F.; Kim, S.D.; Mahant, N.; Fung, V.S.C.
Highlights: We report four patients with orthostatic myoclonus (OM). All four patients showed characteristic electrophysiology. OM should not be confused with orthostatic tremor which has a similar presentation. Abstract: Orthostatic unsteadiness (unsteadiness on standing) is a relatively common symptom and can have neurological or non-neurological causes. Glass et al. have recently described a syndrome presenting with unsteadiness or leg jerking during standing or gait initiation difficulty which they have termed orthostatic myoclonus (OM). OM is a disabling syndrome but potentially treatable. It may develop on the background of neurodegenerative disease; other causes include pro-myoclonic drugs such as tricyclic antidepressants. In order to increase awareness of this syndrome, we report four patients with electrophysiologically confirmed OM who were referred to the movement disorder unit for lower limb tremor studies. All four patients presented with unsteadiness on standing. There were no signs suggestive of neurodegenerative disease and three of the patients had a provisional diagnosis of orthostatic tremor. The diagnosis of OM was supported by a surface electromyography showing 9–16 Hz, non-rhythmic muscle bursts with burst duration of 50–100 ms during standing. OM is unrecognised by many physicians as a cause of orthostatic intolerance. The most common syndrome with which OM may be confused is orthostatic tremor. A correct diagnosis is important as it may respond to treatment with clonazepam, gabapentin or piracetam.